In vivo and in silico models of Drosophila for Parkinson's disease - Cesur, Mueberra Fatma; Strazdins, Rachel; Sarkar, Souvarish; Çakır, Tunahan (Wiley, 2025)
The fruit fly Drosophila melanogaster has emerged as an important model organism to shed light on neurodegeneration. Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder, the cause of which is still mostly unclear. The long-term use of available PD drugs may have major side effects, and they only target the symptoms without providing any effective cure for the disease. Therefore, in vivo and in silico approaches are extensively used to model PD-like phenotypes in Drosophila and investigate cellular alterations underlying PD pathogenesis. In vivo models are particularly crucial to provide insight into the PD-related molecular processes. It has been a preferred approach to investigate these models by collecting omics datasets, which can be further analysed using in silico modeling such as genome-scale metabolic models and artificial intelligence applications. This review aims to summarise in vivo and in silico modeling studies in the literature to illustrate the potential of the Drosophila in the characterisation of PD-related biological mechanisms towards providing early biomarkers and novel treatment options for PD.
Keywords: artificial intelligence; Drosophila melanogaster; genetic factor; genome-scale metabolic modeling; neurotoxin; Parkinson's disease; proteome; transcriptome